Health care-seeking behaviour for child illnesses among rural mothers in South Africa: a pilot study - Supa Promtussananon; Karl Peltzer (AOSIS, 2003)
The aim of this study was to examine the health care-seeking behaviour of mothers when their children under five years suffer from common childhood illnesses such as diarrhoea, fever, cough and worms. Opsomming Die doel van die navorsing was om moeders met siek kinders se gesondheidsgedrag na te vors. Die fokus was op die moeders se pogings om mediese hulp vir hul kinders te bekom. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.